(untitled) (Zien Journal of Social Sciences and Humanities, 2025)
This is an International Relations policy-research article analyzing the hydropolitical implications of Afghanistan’s Koshtepa Canal for Central Asia’s regional water security and cooperative governance. The construction of Afghanistan’s 280-kilometer Koshtepa Canal represents a turning point in Central Asia’s hydropolitics. Drawing on principles from the 1997 UN Convention on the Non-Navigational Uses of International Watercourses and regional water-sharing regimes, this article analyzes the canal’s implications for water security in the Amu Darya basin. While the project seeks to alleviate Afghanistan’s agricultural deprivation, it risks intensifying scarcity in downstream Uzbekistan and Turkmenistan. The paper argues that effective cooperative mechanisms rooted in equitable utilization, the no-harm rule and joint monitoring are essential to transform potential conflict into hydro-diplomatic engagement